Molecular and morphological identification of the alfalfa weevil larval parasitoids Bathyplectes anura and Bathyplectes curculionis to estimate the rate of parasitism - Alexandre Levi-Mourao; Pilar Muñoz; Pedro Cerda-Bennasser; Roberto Meseguer; Xavier Pons (BioControl, 2022)
The alfalfa weevil ( Hypera postica Gyllenhal, Coleoptera: Curculionidae) is a major pest of alfalfa crops. Chemical control measures are inefficient, but the larvae are often infested by parasitoid wasps of the genus Bathyplectes Förster (Hymenoptera: Ichneumonidae), which offer a potential biological control strategy. The development of effective biological control requires the identification of parasitoid species, but conventional methods involve the rearing of parasitoids to the puparium stage for morphological confirmation. Here we designed a PCR method in which two pairs of primers are used to detect and identify Bathyplectes curculionis Thomson and Bathyplectes anura Thomson larvae in a faster way. We compared conventional rearing to the new method as a means to determine the parasitism rates caused by each species in Spain during the 2019 and 2020 seasons. In 2019, the PCR method detected five times as many B. curculionis events and twice as many B. anura events. Similarly, in 2020, the PCR method detected seven times as many B. curculionis events and twice as many B. anura events. High mortality of H. postica larvae was recorded in 2020 due to an epizootic attack by the fungus Zoophthora phytonomi Arthur (Zygomycetes: Entomophthorales), explaining the lower overall rate of parasitism and the widespread death of the larvae. Statistical analysis confirmed that the PCR method is more sensitive than conventional rearing for the detection of target parasitoids. However, only rearing can confirm the effective parasitism or the presence of unexpected species. We therefore recommend the use of both methods in parallel when evaluating host–parasitoid systems.

Movement of three aphidophagous ladybird species between alfalfa and maize revealed by carbon and nitrogen stable isotope analysis - Antonella di Lascio; Filipe Madeira; Maria Letizia Costantini; Loreto Rossi; Xavier Pons (BioControl, 2016)

Effects of surrounding landscape on parasitism of alfalfa aphids in an IPM crop system in northern Catalonia - Xavier Pons; Belén Lumbierres; Jordi Comas; Filipe Madeira; Petr Starý (BioControl, 2013)

Effect of Bt maize on the plant-aphid–parasitoid tritrophic relationships - Belén Lumbierres; Petr Starý; Xavier Pons (BioControl, 2011)